Effect of Solvent on Fluorescence and Fluorescence Lifetimes of p-Substituted Polystyrene - A. Yousef, Yaser; E. Al-Ani, Khalid; Akasheh, Talal (Asian Journal of Chemistry, 2010)
Spectrophotometric measurements for solutions of polystyrene, poly(4-methylstyrene), poly(4-methoxystyrene), poly(α-methylstyrene), poly(4-tert-butylstyrene), poly(4-chlorostyrene) and poly(4-bromostyrene), were carried out in dichloromethane, dichloroethane, N,N-dimethyl formamide and tetrahydrofuran solvents. Although insignificant effects could be noticed on the absorption spectra of the polymers in various solvents, the differences in the fluorescence and fluorescence lifetime data were significantly clear. Intense fluorescence could be observed from these polymers when excited at their maximum absorption bands. Highest intensities were found to exist in poly(4-methoxystyrene) as well as in poly(4-tert-butylstyrene). The fluorescence lifetime data for any of the polymers could be fitted to a double exponential decay function. The decay included two lifetimes, the shorter lived signal identified as the monomer fluorescence and the longer lived one were assigned as the decay time of the excimer. The fluorescence lifetimes were found to be a function of solvent polarity, i.e., decrease with increasing the solvent polarity. Furthemore, the fluorescence quantum yields for poly(4-methoxystyrene) were measured in four solvents and were found to decrease with increasing solvent polarity.